Peningkatan Kemampuan Akurasi Shooting Melalui Metode Drill Pada Ekstrakurikuler Futsal MAN Kota Tegal - Thoriq Nur Fadilah; Agus Tomi; Dona Sandy Yudasmara (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The research based on the shooting accuracy technique skills of futsal extracurricular students at Islamic Senior High School Tegal City has not reached the maximum level. Therefore, researchers used the drill method in training to improve the shooting accuracy technique skills of futsal students at Islamic Senior High School Tegal City. This study aims to test the effectiveness of the drill method in improving a shooting accuracy technique skill in futsal extracurricular students. The method used is sports action research (PTO) involving 2 cycles. Each cycle has 9 meetings and each cycle consists of planning, implementing, observing, and reflecting. A total of 20 students were involved in this study. The results showed that there was an increase in accuracy shooting technique skills in cycle 1 and cycle 2. Initial observation of the percentage of completeness was only 21%, but in cycle 1 there was an increase to 48% and in cycle 2 the skill of shooting accuracy technique increased up to 83%. Thus, the results of the study showed that the shooting accuracy technique skills of futsal students at Islamic Senior High School Tegal City increased to a very good category. Based on these results, it can be concluded that sports action research (PTO) using the drill method can improve the shooting accuracy of futsal extracurricular students at Islamic Senior High School Tegal City.